2020
DOI: 10.1111/acv.12627
|View full text |Cite
|
Sign up to set email alerts
|

‘Self‐fumigation’ of nests by an endangered avian host using insecticide‐treated feathers increases reproductive success more than tenfold

Abstract: Parasites can cause great fitness cost to their hosts, however, their impact on host populations is often unknown. In healthy populations, parasites are not expected to cause declines, but they can be devastating to small and/or declining populations. Nest ectoparasites can have detrimental impacts on the breeding output of their hosts and are emerging as a threat to several endangered bird species. Therefore, finding cost-effect ways to reduce the impact of parasites on endangered hosts is crucial. Although '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…With these dosing parameters, some of these poultry studies reported sublethal effects consisting of weight loss and a reduction in the hatching of normal chicks. In regard to the effectiveness of the chemicals against P. downsi, permethrin application increased finch fledging survival and was effective at reducing the number of P. downsi larvae in avian nests in Galápagos (Causton et al, 2019;Cimadom et al, 2019), as well as against other nest parasites in conservation programs elsewhere (Alves et al, 2020). Cyromazine preliminary field applications have also led to finch's reproductive success as well as reduction in fly development in Galápagos (Causton et al, 2019(Causton et al, , 2020.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With these dosing parameters, some of these poultry studies reported sublethal effects consisting of weight loss and a reduction in the hatching of normal chicks. In regard to the effectiveness of the chemicals against P. downsi, permethrin application increased finch fledging survival and was effective at reducing the number of P. downsi larvae in avian nests in Galápagos (Causton et al, 2019;Cimadom et al, 2019), as well as against other nest parasites in conservation programs elsewhere (Alves et al, 2020). Cyromazine preliminary field applications have also led to finch's reproductive success as well as reduction in fly development in Galápagos (Causton et al, 2019(Causton et al, , 2020.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, they used impregnated feathers treated with a combination of permethrin, piperonyl butoxide, and methoprene. The pardalotes not only incorporated the treated feathers into their nests, but the survival of hatchlings was higher in nests that contained treated feathers compared to those that did not (Alves et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…For details of the identification and further information on study sites, see Edworthy (2016), Alves et al (2020) and Nelson & Grzywacz (2017). Previously identified larval specimens of P. heterochaeta and P. steini were obtained from collections at the Natural History Museum, London, UK.…”
Section: Methodsmentioning
confidence: 99%
“…Passeromyia indecora were obtained from a pigeon nestling in October 2015 at Bluewater, Queensland (Australia). For details of the identification and further information on study sites, see Edworthy (2016), Alves et al (2020) and Nelson and Grzywacz (2017). Previously identified larval specimens of P .…”
Section: Methodsmentioning
confidence: 99%
“…Both methods, with subtle variations, are being used in attempts to increase the nesting success of the critically endangered mangrove finch, currently one of the most endangered birds in the world (Fessl et al, 2018). The same method is also being used successfully to protect endangered bird species against their respective parasites in Australia (Alves et al, 2020).…”
Section: Introductionmentioning
confidence: 99%